Strategy and Tactics of Taiwan’s Foreign Policy Against the Background of Aggravated Tensions with China - Ya. V. Leksyutina (Международная аналитика)
Currently, more than seven decades after its emergence in 1949, the Taiwan issue has not lost its relevance, but, instead, against the backdrop of growing U.S.–China tensions, is becoming especially acute. The PRC, which has already built up an impressive financial and economic might and a powerful military, is focused on achieving the so-called second “centennial goal” by 2049, which includes, among other things, the return of Taiwan to Beijing’s control. The return to power in Taiwan in 2016 of the Democratic Progressive Party, which stands on the positions of Taiwan’s movement towards independence, led to an almost complete “zeroing” of all the achievements as the results of the normalization of Sino-Taiwan relations in 2008–2016, dispelled hopes for a peaceful solution to the Taiwan problem and caused another round of aggravation of tension in the Taiwan Strait. The purpose of this article is to characterize the strategy and tactics of Taiwan’s foreign policy in 2016–2022, when the Tsai Ing-wen administration, which rejected the “one state, two systems” formula of unification, was under strong pressure from Beijing. In its relations with the PRC conducting the “steadfast diplomacy”, the Tsai Ing-wen administration has been taking eﬀorts to promote a narrative in the world discourse that emphasizes the geopolitical, economic, technological, and ideological significance of Taiwan and its autonomous existence from mainland China for the world community and, first of all, its liberal-democratic part. Continuously losing its “diplomatic allies” due to Beijing’s intensified activities in limiting Taiwan’s international space since 2016, the Taiwan administration purposefully builds up and actively uses such advantages as developed democracy, technological power, and competitive, innovative, open economy in order to attract new like-minded partners for close cooperation.